Effect of Body Weight–Supported Exercise on Symptoms of Knee Osteoarthritis: A Follow-up Investigation. Issue 6 (November 2020) - Peeler, Jason; Leiter, Jeffrey; MacDonald, Peter
Abstract : Objective: To examine the long-term effect of participation in a 12-week lower-body positive pressure (LBPP)–supported low-load treadmill exercise regime on knee joint pain, physical function, and thigh muscle strength in patients with knee osteoarthritis (OA). Design: Prospective, observational, repeated measures. Setting: Clinical orthopedic setting. Patients: Nineteen overweight patients with knee OA. Intervention: Participants exercised under low-load treadmill walking conditions 2×/week for 12 weeks using an amount of LBPP support that minimized knee pain while walking for a period of 30 minutes at a set speed of 3.1 mph at 0-degree incline. Main Outcome Measures: Knee pain, function, thigh muscle strength, and body anthropometry were reassessed a minimum of 6 months after completion of the initial exercise regime and compared with results from baseline and postexercise evaluation. Results: Data suggested that: (1) patients were able to maintain improvements in knee joint pain and symptoms; (2) patients continued to report enhanced joint function and improved quality of life; and (3) patients maintained thigh muscle strength gains. Finally, a majority of patients continued to experience significant reductions in acute knee pain during full weight-bearing treadmill walking. Conclusions: Data suggest that improvements in knee pain, joint function, and thigh muscle strength associated with participation in a 12-week LBPP-supported low-load exercise regime were maintained well after cessation of the program. These findings have important implications for the development and refinement of exercise strategies and interventions used in the long-term management of joint symptoms associated with knee OA in overweight patients.